Chronic impairment of neurovascular coupling and cognitive decline in young survivors of severe traumatic brain injury - Zsofia Dina Magyar-Sumegi; Mark Csendes; Dominika Lendvai-Emmert; Gabriella Sebestyen; Viktoria Tamas; Szabolcs Bandi; Andras Czigler; Andriy Yabluchanskiy; Stefano Tarantini; Zoltan Ungvari; Endre Czeiter; Krisztina Amrein; et al. (GeroScience, 2025)
Severe traumatic brain injury (TBI) leads to chronic cognitive decline, imposing a significant societal burden. The regulation of cerebral blood flow (CBF) is critical for cognitive function, and acute disruptions in CBF regulation predict poor TBI outcomes. However, the long-term effects of TBI on CBF regulation and their association with cognitive function remain poorly understood. This study aimed to investigate whether severe TBI results in chronic CBF dysregulation and whether this contributes to long-term cognitive deficits. Additionally, we examined the role of TBI-induced insulin-like growth factor 1 (IGF-1) deficiency in cerebrovascular dysfunction. We assessed cognitive function, basal CBF (via phase contrast MRI), CBF autoregulation (via transcranial Doppler), and neurovascular coupling (NVC) in 33 TBI survivors (mean age 37.6 years, ~ 10 years post-injury) and 21 age-matched healthy controls. Serum IGF-1 levels were also measured. TBI survivors exhibited significant impairments in memory and executive function compared to controls. While basal CBF and autoregulation remained intact, NVC responses were chronically impaired and correlated with cognitive deficits. However, IGF-1 levels did not differ between groups and were not associated with NVC impairment or cognitive function. Our findings indicate that severe TBI results in chronic impairment of neurovascular coupling, which likely contributes to long-term cognitive deficits. These results highlight the need for further research to identify underlying neurovascular mechanisms and develop interventions to restore NVC and cognitive function in TBI survivors.

Age-related decline in circulating IGF-1 associates with impaired neurovascular coupling responses in older adults - Luca Toth; Andras Czigler; Emoke Hegedus; Hedvig Komaromy; Krisztina Amrein; Endre Czeiter; Andriy Yabluchanskiy; Akos Koller; Gergely Orsi; Gabor Perlaki; Attila Schwarcz; Andras Buki; et al. (GeroScience, 2022)
Impairment of moment-to-moment adjustment of cerebral blood flow (CBF) to the increased oxygen and energy requirements of active brain regions via neurovascular coupling (NVC) contributes to the genesis of age-related cognitive impairment. Aging is associated with marked deficiency in the vasoprotective hormone insulin-like growth factor-1 (IGF-1). Preclinical studies on animal models of aging suggest that circulating IGF-1 deficiency is causally linked to impairment of NVC responses. The present study was designed to test the hypotheses that decreases in circulating IGF-1 levels in older adults also predict the magnitude of age-related decline of NVC responses. In a single-center cross-sectional study, we enrolled healthy young ( n = 31, 11 female, 20 male, mean age: 28.4 + / − 4.2 years) and aged volunteers ( n = 32, 18 female, 14 male, mean age: 67.9 + / − 4.1 years). Serum IGF-1 level, basal CBF (phase contrast magnetic resonance imaging (MRI)), and NVC responses during the trail making task (with transcranial Doppler sonography) were assessed. We found that circulating IGF-1 levels were significantly decreased with age and associated with decreased basal CBF. Age-related decline in IGF-1 levels predicted the magnitude of age-related decline in NVC responses. In conclusion, our study provides additional evidence in support of the concept that age-related circulating IGF-1 deficiency contributes to neurovascular aging, impairing CBF and functional hyperemia in older adults.

Traumatic brain injury-induced cerebral microbleeds in the elderly - Luca Toth; Andras Czigler; Peter Horvath; Balint Kornyei; Nikolett Szarka; Attila Schwarcz; Zoltan Ungvari; Andras Buki; Peter Toth (GeroScience, 2021)
Traumatic brain injury (TBI) was shown to lead to the development of cerebral microbleeds (CMBs), which are associated with long term cognitive decline and gait disturbances in patients. The elderly is one of the most vulnerable parts of the population to suffer TBI. Importantly, ageing is known to exacerbate microvascular fragility and to promote the formation of CMBs. In this overview, the effect of ageing is discussed on the development and characteristics of TBI-related CMBs, with special emphasis on CMBs associated with mild TBI. Four cases of TBI-related CMBs are described to illustrate the concept that ageing exacerbates the deleterious microvascular effects of TBI and that similar brain trauma may induce more CMBs in old patients than in young ones. Recommendations are made for future prospective studies to establish the mechanistic effects of ageing on the formation of CMBs after TBI, and to determine long-term consequences of CMBs on clinically relevant outcome measures including cognitive performance, gait and balance function.